ANALYSIS IMPLEMENTATION OF THE ASSURE MODEL IN ENHANCING THE EFFECTIVENESS OF ISLAMIC RELIGIOUS EDUCATION LEARNING - Malik, Muhamad Ibnu; Nugraha, Mulyawan Safwandy; Tarsono (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2023)
Application of the ASSURE model can be a support for improving the quality of Islamic religious education learning that is effective, efficient and helps students' learning motivation. The aim of this research is to determine the application of the ASSURE model in increasing the effectiveness of Islamic religious education learning at SMP IT Anni'mah Bandung Regency. The research method used is a qualitative method with a descriptive approach. The type of research that is applied is a case study. Data collection was carried out by triangulation, namely observation, interviews and documentation. Data analysis is carried out by data reduction, data presentation and data verification. The research findings show that the effectiveness of Islamic religious education learning is carried out by applying media and technology through the ASSURE model in PAI learning by identifying general student characteristics which are presented in psychologist tests. Develop learning objectives with the relevance of the subject matter and implications for student personality. Choosing a learning method, media namely PowerPoint and technology using cellphones as access to presenting material and involving students actively in the learning process. Measuring students' abilities through learning evaluations carried out by written tests, interviews and munaqosyah. The supporting factors obtained include active and confident students in developing knowledge, making it easier for students to understand lesson material, adapting learning methods and media, making it easier for teachers to assess students' understanding and abilities on the basis of provided learning applications and the use of technology in the teaching and learning process. Inhibiting factors include students being late for class which disrupts learning effectiveness, and students' lack of motivation in learning.